2002
DOI: 10.1590/s0100-06832002000200026
|View full text |Cite
|
Sign up to set email alerts
|

Sorção de atrazina em cambissolo húmico do Rio Grande do Sul sob vegetação nativa

Abstract: RESUMOA acumulação de herbicidas no ambiente em virtude de sua larga utilização em sistemas agrícolas, associada à alta persistência, é extremamente preocupante, considerando os efeitos maléficos que alguns destes compostos causam à flora e à fauna. A atrazina (2-cloro-4-etilamino-6-isopropilamino-striazina) é um dos herbicidas mais utilizados na atualidade e tem sido detectada em teores consideráveis em mananciais e solos. O objetivo deste estudo foi avaliar o comportamento sortivo da atrazina comercial em Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
1
0
3
Order By: Relevance
“…The Kd values found here agree with those found in literature (ARANTES et al, 2006;BARRIUSO et al, 1992;CORREIA et al, 2007;GOMES;SOUZA, 2002;DICK et al, 2010;HUANG et al, 2012), which are around 1.34 to 5.96 L Kg -1 . Dick et al (2010) found higher Kd (4.30 L kg -1 ) to an Planosol than a Argisol (Kd = 3.56 L kg -1 ) due the higher amounts of organic matter.…”
supporting
confidence: 92%
“…The Kd values found here agree with those found in literature (ARANTES et al, 2006;BARRIUSO et al, 1992;CORREIA et al, 2007;GOMES;SOUZA, 2002;DICK et al, 2010;HUANG et al, 2012), which are around 1.34 to 5.96 L Kg -1 . Dick et al (2010) found higher Kd (4.30 L kg -1 ) to an Planosol than a Argisol (Kd = 3.56 L kg -1 ) due the higher amounts of organic matter.…”
supporting
confidence: 92%
“…This behavior was expected sinc e atrazin e shows high adsorption to soil particles and low solubility. The high adsorption to the 0 horizon can be noted when comparing the atrazi ne K f value (67 .54 ) to the fou nd for atr azi ne adsorption to whole soil particles (1.0 to 4.0) (Barriuso et al, 1992;Nakagawa et al, 1995;Seta and Karathanasis, 1997;Gomes et al, 2002). On the oth er han d, the amount of atrazine adsor bed by the amount of litt er, represented by the normalized mass (Table 3) was lower in the 0 horizon (1.01 µg g -1 ) when compared to 6.35 µg g -1 obtained by (Huang et al, 1984) for clay particles.…”
Section: Resultsmentioning
confidence: 99%
“…Não houve diferença significativa entre os coeficientes de Freundlich (K f ) do sistema de plantio direto e do convencional. É bem relatado na literatura que a matéria orgânica representa a principal fração responsável pela sorção da atrazina em solos (Traghetta et al, 1996;Gomes et al, 2002;Dick et al, 2010). Porém, neste estudo, amostras do solo sob o plantio direto, apesar de possuírem maior quantidade de matéria orgânica, não apresentaram maior retenção do herbicida.…”
Section: Sorção Da Atrazinaunclassified